A Review Paper on the Role of Shirodhara A Non-Pharmacological Intervention in the Management of Insomnia. - Pooja, Rani; Subash, Sahu (International Research Journal of Ayurveda & Yoga, 2022)
Objective: The goal of this study was to look at the mode of action of Shirodhara and how it affects the levels of neurotransmitters in those who suffer from insomnia. Data Source:Brihatrayi and Laghutrayi were accessed through the NIIMH website, as well as newer texts both online and offline. Review Method: The mode of action of shirodhara and its influence on sleep regulating neurotransmitters were the main topics of discussion in the literature study. For scientific explanation and therapeutic application, both Ayurvedic and modern texts have been assembled with its effect on neurotransmitter levels. Result: The current period of pandemic conditions, as well as Covid-like events, has resulted in a slew of mental health concerns and sleep disturbances. It has been discovered that stressful situations produce a neurotransmitter imbalance. Quality sleep may heal half of all ailments, which is why it is considered one of life’s essential sub-pillars. Additionally, due to its effectiveness and lack of side effects, a movement from pharmacological to nonpharmacological therapy has been noted. Conclusion: Shirodhara therapy is a panchakarma procedure in which a medicinal liquid is poured continuously and rhythmically over the forehead. Acharya Vagbhatta characterized it as a sort of Moordhini taila. Shiroabhyang, Shiroseka, Shiropichu, and Shirobasti are all part of the Moordhinitaila. Sleep is an important component in determining life expectancy. Shirodhara therapy is regarded as an excellent nonpharmacological treatment for insomnia in Ayurveda.